The Interpretation of Inheritance Verses from The Perspective of Asghar Ali Engineer - Lailatul Mubaraka; Yusuf Baihaqi; Kiki Muhamad Hakiki (Pascasarjana IAIN Metro, 2026)
This study aims to analyze the interpretation of inheritance verses according to Asghar Ali Engineer and its relevance to gender justice in modern contexts. The method used is library research with a qualitative approach, examining Engineer's works as primary sources and classical-contemporary tafsir literature as comparison. The results show that Engineer uses social hermeneutics that understands inheritance verses as a response to 7th-century Arab society conditions, so the 2:1 ratio is considered adjustable to changes in modern women's economic roles. However, this study finds fundamental weaknesses in Engineer's approach that separates inheritance verses from the Islamic family economic system as a whole and ignores the principle of inter-verse connections. In conclusion, justice in Islamic inheritance is not measured by mathematical equality, but by the balance of rights and obligations. The solution to injustice in inheritance practices is through education on understanding the complete Islamic family system, not by changing the clear provisions of the Qur'an.